(Cultural) Humility in Practice: Engaging First-Generation College Students. Issue 3 (3rd July 2022) - Rovitto, Tam Le
ABSTRACT: Among the 20 million students nationwide enrolled in colleges in the fall of 2019, one-third were first-generation college students (FGCS). The college years spark life transitions for all students, but for FGCS, there are additional challenges and barriers in mental health-seeking and treatment. Hence, the treatment attrition rate is high once FGCS access services at college counseling centers (CCC). Research suggests that the cultural humility framework and the Cultural Formulation Interview (CFI) may be effective interventions for getting FGCS to access and engage mental health services. The cultural humility framework emphasizes self-reflection and alliance building. And the CFI explores specific cultural norms, causes of mental health complaints, and barriers to treatment. This composite case study aims to illustrate the benefits and effectiveness of integrating the cultural humility framework and the CFI throughout treatment of an FGCS. Providing such services reveals that FGCS engagement and retention rates at CCC will improve.